Incidence of chronic immune-mediated inflammatory diseases after diagnosis with Kawasaki disease: a population-based cohort study. (8th September 2021) - Fung, Stephen G; Webster, Richard; Kuenzig, M Ellen; Knight, Braden D; Batthish, Michelle; Robinson, Cal; Chanchlani, Rahul; Benchimol, Eric I; Jimenez-Rivera, Carolina
Abstract: Objectives: Kawasaki disease (KD) is an immune-mediated vasculitis of childhood with multi-organ inflammation. We determined the risk of subsequent immune-mediated inflammatory disease (IMID), including arthritis, type 1 diabetes, IBD, autoimmune liver disease, primary sclerosing cholangitis and multiple sclerosis. Methods: We conducted a matched population-based cohort study using health administrative data from Ontario, Canada. Children aged <18 years born between 1991 and 2016 diagnosed with KD ( n  = 3753) were matched to 5 non-KD controls from the general population ( n  = 18 749). We determined the incidence of IMIDs after resolution of KD. Three- and 12-month washout periods were used to exclude KD-related symptoms. Results: There was an elevated risk of arthritis in KD patients compared with non-KD controls, starting 3 months after index date [103.0 vs 12.7 per 100 000 person-years (PYs); incidence rate ratio 8.07 (95% CI 4.95, 13.2); hazard ratio 8.08 (95% CI 4.95, 13.2), resulting in the overall incidence of IMIDs being elevated in KD patients (175.1 vs 68.0 per 100 000 PYs; incidence rate ratio 2.58 (95% CI 1.93, 3.43); hazard ratio 2.58, 95% CI 1.94, 3.43]. However, there was no increased risk for diabetes, IBD, autoimmune liver disease, primary sclerosing cholangitis or multiple sclerosis in KD patients. Similar results were observed using a 12-month washout period. Conclusion: Children diagnosed with KD were at increased risk of arthritis following the acute KD event, but not other IMIDs. Health-care providers should monitor for arthritis in children following a diagnosis of KD.